2019
DOI: 10.1016/j.jveb.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Dumb or smart asses? Donkey's (Equus asinus) cognitive capabilities share the heritability and variation patterns of human's (Homo sapiens) cognitive capabilities

Abstract: Scientific evidence for intelligence in donkeys could expose their historical unmerited cognitive derogatory status. Psychometric testing enables quantifying animal cognitive capabilities and their genetic background. Owing to the impossibility to use the language-dependent scales that are widely used to measure intelligence in humans, we used a nonverbal operant-conditioning problem-solving test to compute a human-analogous IQ, scoring the information of thirteen cognitive processes from 300 genetically teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 63 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…Individuals who failed to adjust quickly would likely struggle in response to shifting resources, highlighting that shifts in resource availability can be a strong selection pressure for inherently bold, innovative, persistent, or flexible individuals. The understanding of the heritability of these behavioral traits is still developing, but research has identified genetic correlations with boldness in multiple vertebrate species ( Bubac et al, 2021 ; Stratton, Nolte & Payseur, 2021 ) and differential heritability among different behaviors in donkeys ( Equus asinus ; Navas González et al., 2019 ). Therefore, environmental changes that select for bold, innovative, or persistent individuals paired with the heritability of these traits could result in shifts in behavior at the population level over time.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who failed to adjust quickly would likely struggle in response to shifting resources, highlighting that shifts in resource availability can be a strong selection pressure for inherently bold, innovative, persistent, or flexible individuals. The understanding of the heritability of these behavioral traits is still developing, but research has identified genetic correlations with boldness in multiple vertebrate species ( Bubac et al, 2021 ; Stratton, Nolte & Payseur, 2021 ) and differential heritability among different behaviors in donkeys ( Equus asinus ; Navas González et al., 2019 ). Therefore, environmental changes that select for bold, innovative, or persistent individuals paired with the heritability of these traits could result in shifts in behavior at the population level over time.…”
Section: Discussionmentioning
confidence: 99%
“…Individual personality was scored using an adaptation of the questionnaire proposed by Navas et al [ 38 ], and French [ 39 ]. The aforementioned methodology has been previously used to evaluate behavioural patterns in problem-focused coping styles, the genetic background behind them and the conditioning factors involved in donkeys [ 24 , 27 , 28 , 35 , 40 ]. A questionnaire was completed by ten observers.…”
Section: Methodsmentioning
confidence: 99%
“…The wide variability and particularities of donkey breeds [ 25 ] has promoted the adaptation of cognitive tests used in Miniature donkeys [ 26 ]. However, no evidence for interindividual and interbreed variability components have been reported, even if there is a strong possibility that selective breeding has led to temperamental and cognitive differences [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the complexity of donkeys' cognitive abilities and emotions. Donkeys have high cognitive abilities and are considered intelligent animals when comparatively scored on an analogous human scale ( 41 ). Regardless of studies in donkeys, the evolutionary mechanisms provide unequivocal evidence of the continuum of brain complexity of animals, then the differences are more related to degree rather presence of such capacities.…”
Section: Neurophysiological and Cognitive Basis For Preventing Animal...mentioning
confidence: 99%